Remote Court: Principles for Virtual Proceedings During the COVID-19 Pandemic and Beyond - Bannon, Alicia L. (2021)
Across the country, courts at every level have relied on remote technology to adapt the justice system to a once-a-century global pandemic. This Essay describes and assesses this unprecedented journey into virtual justice, paying particular attention to eviction proceedings. While many judges have touted remote court as a revolutionary innovation, the reality is more complex. Remote court has brought substantial time savings and convenience to those who are able to access and use the required technology, but it has also posed hurdles to individuals on the other side of the digital divide, particularly self-represented litigants. The remote court experience has varied substantially depending on the nature of the proceedings, the rules and procedures courts put in place, and the relevant court users’ resources and tech savvy. Critically, the challenges posed by remote court have often been less visible to judges than the efficiency benefits. Drawing on these lessons, this Essay identifies a series of principles that should inform future uses of remote technology. Ultimately, new technology should be embraced when—and only when—it is consistent with fair proceedings and access to justice for all